An Analytical study of Right to Fair Trial & judiciary in Shariah Perspective - Dr Ayesha Jadoon; Dr Sadna Zeb (jihat-ul-islam, 2022)
There is clear guidance in Islam regarding justice. In addition to the principles regarding the appointment of a judge, there are details about the decision in the shariah and the rights of the parties, the Judiciary Council, the etiquette and testimony of the judges as well as the scribes and staff of the court. The term Fair Trial is very important in the judiciary. This is the right that lays the groundwork for the provision of various kinds of guarantees for the accused. Although this specific term is not used in Islamic jurisprudence, the guarantees that the accused get from it are part of the jurisprudence system in Shariah such as telling the accused about his crime, public hearing, facility of translator in case of unfamiliarity with the language of the court, examination of witnesses, right of appeal etc. This article appraises the Analytical study of Right to Fair Trial & judiciary in Shariah Perspective specifically appointment of judge and decision-making capacity and etiquettes.